Study of the convective drying of pumpkin (Cucurbita máxima). - Pinho, Susana (2012)
This work intends to study how drying influences the properties of pumpkin, namely moisture content, total and reducing sugars, acidity, proteins, lipids, crude fiber and ash. The results enable concluding that, apparently, the convective drying process has no effect on the nutritional characteristics of the pumpkin, except on sugars and acidity. The drying kinetics was also analysed, and the results show that the increase on the operating temperature strongly accelerates the drying process. The experimental data for moisture ratio was fitted to different models, and the best wer Page and modified Page.